PENGARUH PENDEKATAN STEAM BERBASIS PJBL TERHADAP KEMAMPUAN PROBLEM SOLVING PADA MATERI PERMASALAHAN LINGKUNGAN - Eronisa, Syahla Muthia; Satianingsih, Rarasaning (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyse whether there is an influence of the STEAM approach integrated with Project-Based Learning (PjBL) on students' problem-solving abilities in the context of environmental issues. STEAM-PjBL is a combination of the STEAM approach (Science, Technology, Engineering, Art, Mathematics) with the Project-Based Learning model. This method blends elements of STEAM education with project-based learning to create a learning experience that is contextually rich, collaborative, and relevant to real-world situations. The study employed a quasi-experimental method with a Nonequivalent Control Group Design. The subjects were Year 5 students of SDN Dukuh Menanggal 1/424 in Surabaya, with the experimental class implementing STEAM-PjBL and the control class utilising Problem-Based Learning. Data were collected through pre-tests and post-tests to measure problem-solving indicators, including understanding the problem, developing a plan, and implementing the problem-solving plan. The data were analysed using normality tests, homogeneity tests, and t-tests via SPSS. The findings reveal that the STEAM-PjBL approach has a significant impact on students' problem-solving abilities in the topic of environmental issues.